2017
DOI: 10.1371/journal.pone.0174408
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department outpatient treatment of alcohol-intoxicated bicyclists increases the cost of medical care in Japan

Abstract: Riding a bicycle under the influence of alcohol is illegal in Japan. Nevertheless, intoxicated bicyclists are frequently treated at hospital emergency departments for bicycle-related injuries. This patient population usually requires more hospital resources, even for relatively minor injuries. Therefore, we hypothesized that bicycle-related crashes involving bicyclists under the influence of alcohol cost more to treat than those that do not involve alcohol intoxication. The aim of the present study was to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Our main results demonstrated that one third of the injured cyclists were under the influence of alcohol at the time of attending the emergency hospital. Similar results were found in Tokyo [2] and Los Angeles, California [1]. According to a German database study, 57% of the cyclists involved in accidents had a BAC above 0.5 g/l, which is the maximum legal drink driving limit in Germany for a car or motorcycle [15].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Our main results demonstrated that one third of the injured cyclists were under the influence of alcohol at the time of attending the emergency hospital. Similar results were found in Tokyo [2] and Los Angeles, California [1]. According to a German database study, 57% of the cyclists involved in accidents had a BAC above 0.5 g/l, which is the maximum legal drink driving limit in Germany for a car or motorcycle [15].…”
Section: Discussionsupporting
confidence: 67%
“…The present study shows that the total direct and indirect costs of bicycle-related injuries treated in ED were higher among sober cyclists than among cyclists with AI, and constituted a total of 1984 s per patient (at the 2017 price level). However, in a study from Tokyo, Japan (minor bicycle accidents involving 217 individuals aged !20 years, treated in ED), alcohol intoxication was independently associated with higher medical costs [2]. Two similar results from Arizona and New York indicated that the alcohol-positive cyclists were more seriously injured and their healthcare costs were higher than those of the sober cyclists [5,21].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The literature showed that alcohol related traffic accident victims cost more to the health care system when compared to the cost of the victims after non-alcohol related accidents [26]. This literature does not include traffic accidents of pedestrians and cyclists [27,28]. Another study showed that in addition to financial burden of those alcohol caused traffic accidents to the health care system, those cases resulted in longer hospitalization periods at E.R.…”
Section: Discussionmentioning
confidence: 99%